2023
DOI: 10.1186/s13690-023-01200-5
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization among informal caregivers of older adults in the Ashanti region of Ghana: a study based on the health belief model

Williams Agyemang-Duah,
Mark W. Rosenberg

Abstract: Background Existing global evidence suggests that informal caregivers prioritize the health (care) of their care recipients (older adults) over their own health (care) resulting in sub-optimal health outcomes among this population group. However, data on what factors are associated with healthcare utilization among informal caregivers of older adults are not known in a sub-Saharan African context. Guided by the Health Belief Model (HBM), the principal objective of this study was to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 83 publications
(114 reference statements)
0
11
0
Order By: Relevance
“…Using a spatial distribution map of PM2.5, the best course of action for reducing air pollution by PM2.5 concentrations can be identified. Moreover, according to Agyemang-Duah and Rosenberg [36], the spatial distribution can be used to characterize medical facilities and how they affect people's ability to receive primary healthcare. The hospital bubble analysis map makes it clear that 90% of the communities are not included in Ghana Health's and the WHO's database.…”
Section: Discussionmentioning
confidence: 99%
“…Using a spatial distribution map of PM2.5, the best course of action for reducing air pollution by PM2.5 concentrations can be identified. Moreover, according to Agyemang-Duah and Rosenberg [36], the spatial distribution can be used to characterize medical facilities and how they affect people's ability to receive primary healthcare. The hospital bubble analysis map makes it clear that 90% of the communities are not included in Ghana Health's and the WHO's database.…”
Section: Discussionmentioning
confidence: 99%
“…This was to ensure the representativeness and generalization of the study findings. The demarcation of the study area was guided by the geographical location, socio-economic status, and cultural disparities [ 19 ]. Each district in the study area was tied to one of the three categories.…”
Section: Methodsmentioning
confidence: 99%
“…More districts were selected from the middle zone because most of the districts in the study area are clustered in the middle zone. Detailed information on how simple random sampling was applied to select the study districts and the number of communities included in this study has been reported in a previous study [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations